PROXIMATE AND ANTI-NUTRIENT COMPOSITION OF AFZELIA AFRICANA AND CRESCENTIA CUJETE SEEDS - Obayomi, M. O.; Suleiman, B.; Bashir, A. Y. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2019)
Afzelia africana and Crescentia cujete are underutilized seeds that have been suggested to have good nutritional content. Their utilization for food and other purposes can however be limited by the presence of some anti-nutritional, anti-physiological and toxic substances. Hence, proximate (moisture, protein, lipid, fibre, ash and NFE) and some anti-nutritional contents (alkaloids, phytate, tannins, saponins and flavonoids) of Afzelia africana and Crescentia cujete seeds were investigated. Collected seeds were milled and air dried before analyses. Milled seeds were analysed for proximate composition and anti-nutrients using standard procedures. All proximate contents varied significantly (P<0.05) except for lipid content. Results showed that A. africana seed had the highest ash (4.13%), protein (13.89%) and nitrogen free extract (59.20%) contents, while C. cujete had the highest moisture, lipid and fibre content. The proximate composition of both seeds varied significantly (P<0.05) except for lipid. Alkaloids, tannins, saponins and flavonoids contents were also considerably high for both seeds investigated. The contents of phytates, tannins and flavonoids varied significantly (P<0.05) between both seeds. Crescentia cujete had the highest phytate, tannin and saponin contents while A. africana had the highest alkaloid and flavonoid contents. Since Afzelia africana and Crescentia cujete seeds had relatively high percentage contents of carbohydrate (59.20 and 49.86, respectively) and lipids (16.10 and 17.00, respectively), the seeds could be said to have potentials to serve as good sources of energy for livestock and animal production. The high composition of phytochemicals in the two seeds studied also implies the seeds could be useful for medicinal purposes.